Maternal and Neonatal Outcomes in Pregnancies with Systemic Lupus Erythematosus (SLE) from 2021 to 2023 at Hasan Sadikin Hospital, Bandung - Putra, Ahmad Rialita; Madjid, Tita Husnitawati; Irianti, Setyirini (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: To describe maternal and neonatal outcomes in pregnant women with SLE at Dr. Hasan Sadikin General Hospital, Bandung.Methods: This descriptive study reviewed secondary data of pregnant women with SLE at RSHS from January 2021 to December 2023.Results. A total of 41 pregnant women with SLE and 82 without SLE were included. SLE patients were younger (29.44±5.03 years) than non-SLE (33.76±7.31 years). Most SLE patients had normal (63.4%) or overweight (36.6%) nutritional status. Skin rash was the most common symptom (78%). Hypertension (14.6% vs 73.2%) and fetal death (4.9% vs 17.1%) were lower in the SLE group. Live birth rate was higher (95.1% vs 89.0%), but low birth weight incidence was higher (65.9% vs 53.7%) in SLE.Conclusion: Pregnant women with SLE tend to be younger and overweight. Hypertension and fetal death were lower, but low birth weight and growth restriction were more frequent in SLE pregnancies, despite quality ANC. The cause of fetal growth restriction in SLE remains unclear.Luaran Ibu dan Bayi pada kehamilan dengan Lupus Eritematosus Sistemik (LES) pada tahun 2021 - 2023 di Rumah Sakit Hasan Sadikin BandungAbstrakTujuan: Penelitian ini bertujuan untuk mendeskripsikan luaran maternal dan neonatus pada wanita hamil dengan LES di RSUP Dr. Hasan Sadikin Bandung.Metode: Penelitian ini menggunakan metode deskriptif untuk meninjau data sekunder ibu hamil dengan LES di RSHS dari Januari 2021 hingga Desember 2023.Hasil. Sebanyak 41 wanita hamil dengan LES dan 82 tanpa LES diikutsertakan. Pasien LES lebih muda (29,44±5,03 tahun) dibanding non-LES (33,76±7,31 tahun). Mayoritas pasien LES berstatus gizi normal (63,4%) atau overweight (36,6%). Ruam kulit paling umum (78%). Hipertensi (14,6% vs 73,2%) dan kematian janin (4,9% vs 17,1%) lebih rendah pada LES. Kelahiran hidup lebih tinggi (95,1% vs 89,0%), tapi berat lahir rendah lebih tinggi (65,9% vs 53,7%) pada LES.Kesimpulan: Wanita hamil dengan LES cenderung lebih muda dan overweight. Komplikasi hipertensi dan kematian janin lebih rendah, tetapi berat lahir rendah dan hambatan pertumbuhan janin lebih sering pada LES, meski mendapat ANC berkualitas. Penyebab hambatan pertumbuhan janin pada LES belum diketahui.Kata kunci: Kehamilan; Komplikasi; Luaran maternal; Luaran neonatus; Lupus Eritematosus Sistemik